2009
DOI: 10.2527/jas.2008-1561
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: The relationship between heart rate and energy expenditure in growing crossbred Boer and Spanish wethers1

Abstract: Eight Boer (75%) x Spanish (BS) and 8 Spanish (S) wethers (155 +/- 8 d of age and 19.2 +/- 2.3 kg of BW initially) were used in a replicated crossover design with a 2 x 2 factorial arrangement of treatments to determine effects of genotype, diet quality, and time of day on energy expenditure (EE), heart rate (HR), and EE:HR with ad libitum, near maintenance, and fasting levels of feed intake. Diets were 65% concentrate or coarsely ground alfalfa hay. Energy expenditure was ranked (P < 0.05) ad libitum > mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The procedure of monitoring HR was described by Puchala et al (2007Puchala et al ( , 2009. In brief, wethers were fitted with 5 × 5 cm electrodes prepared from stretch conductive fabric (Less EMF, Albany, NY, USA), glued to Vermed PerformancePlus ECG electrodes (Bellow Falls, VT, USA) and attached to the chest just behind and slightly below the left elbow and behind the shoulder blade on the right side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of monitoring HR was described by Puchala et al (2007Puchala et al ( , 2009. In brief, wethers were fitted with 5 × 5 cm electrodes prepared from stretch conductive fabric (Less EMF, Albany, NY, USA), glued to Vermed PerformancePlus ECG electrodes (Bellow Falls, VT, USA) and attached to the chest just behind and slightly below the left elbow and behind the shoulder blade on the right side.…”
Section: Methodsmentioning
confidence: 99%
“…During the adaptation period, the ratio of heat energy (HE) to heart rate (HR) (HE:HR) was determined as described by Puchala et al (2007Puchala et al ( , 2009. The same diet used in the experiment was fed.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The most probable reason for the greater maintenance feed requirement for the HR vs. BW method with the 55% restriction level is the use of the HE:HR ratio determined in the preliminary period with a level of intake slightly above the assumed maintenance requirement. In this regard, Puchala et al (2009) reported ratios for Boer wethers of 5.59 and 5.00 kJ/kg BW 0.75 per heart beat/ min when consuming feed at a level of intake near maintenance and while fasting, respectively, and values of 5.57 and 5.22 were noted for SPA wethers with similar intake levels.…”
Section: Restriction Phasementioning
confidence: 91%
“…Wethers were moved to an adjacent room in the facility with an indirect open-circuit calorimetry system in sets of four. Heat energy (HE) and heart rate (HR) were determined as in other studies (Puchala et al 2007(Puchala et al , 2009 for approximately 24 h to derive the ratio of HE to HR for multiplication by HR estimated in subsequent phases to predict HE. Oxygen consumption and production of CO 2 and CH 4 were determined by an indirect open-circuit respiration calorimetry system (Sable Systems, Henderson, NV, USA) with four head boxes situated in metabolism cages in a calorimetry room.…”
Section: Preliminary Periodmentioning
confidence: 99%
“…HE was determined by use of heart rate (HR) for prediction, as described by Puchala et al (2007Puchala et al ( , 2009. During the middle week of each period on days 2 and 4, HR was recorded for 24 h, with measurements first on five animals per pen and then on the second five animals.…”
Section: Methodsmentioning
confidence: 99%